A Narrative Review: In-vitro Methods for Assessing Bio-Accessibility/Bioavailability of Iron in Plant-Based Foods - Sulaiman, N.; Givens, D. I.; Anitha, S. (Frontiers in Sustainable Food Systems, 2021)
In-vitro measurement has the advantage of rapid and convenient method of screening the iron bioavailability within the range of plant-based foods. It is important to provide this information as a preliminary screening which will be useful to identify and filter promising plant sources before moving to human trials. A review on in-vitro methods of bio-accessibility and bioavailability of iron in plant-based foods including fruits, vegetables, cereals and legumes is entailed here. The review will focus on the contribution of in-vitro methods towards the information of iron bioavailability in plant-based foods and the effects of inhibitors and processing on the iron bioavailability. The variation of the methods and updates on a recent INFOGEST method used to measure the bioavailability of iron in plant-based foods will also be discussed.